Human Stool from Science and Islam Perspective and Sunnah Dietary Practices - Kashim, MIAM; Hasim, NA; Othaman, R; Khalid, R; Samsudin, MA; Yahaya, MZ; Manaf, ZA; Amin, L; Zin, DMM (Univ Kebangsaan Malaysia, 2024)
Indexed by WOS/SCOPUS